Asbury Dickins family papers - Dickins, Asbury, 1780-1861.; Dickins, Francis Asbury
Correspondence and other papers of Asbury Dickins, Francis Asbury Dickins, and other members of the Dickins family. Includes certificates of purchase for public lands in Illinois in 1830 and draft of a reply to an address by Ninian Edwards, charging William H. Crawford with malfeasance in office.
In part, positive and negative photocopies.
Asbury Dickins, civil servant, and other members of the Dickins (Dickens) family.
Collection material in English.
Keywords: Crawford, William Harris, -- 1772-1834.; Edwards, Ninian, -- 1775-1833.; Dickens family; Misconduct in office; Public lands -- Illinois